Interactive groups and their influence on academic performance in the primary classroom: a case study (Revista Innova Educación, 2022)
The development of this work aims to know, through the implementation of interactive groups, if this model allows the improvement of academic performance, the development of social skills, teamwork, cooperative attitudes and the acceptance of diversity. For this, a qualitative method is used through a case study, implemented in a primary classroom of a public center in the city of Badajoz (Spain). The instruments to collect the information have been the average marks obtained by the students (pre and post-test), the observation by teachers and volunteers, and a questionnaire for the students. The results confirm that the students obtain better grades and show satisfaction with this work model. It can be concluded. Therefore, that interactive groups implement the improvement of academic results but also favor the achievement of goals or purposes such as improved coexistence or motivation.
Keywords: classroom climate; inclusive education; interactive groups; learning; motivation